Regular and chaotic dynamics of decaying cascade of waves in plasma - Buts, V.A.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2002)
The conditions are formulated, at which realization the dynamics of interaction of finite number of decaying waves becomes chaotic. The estimation of characteristic time of transition from regular dynamics to chaotic is given.